Histopathological Changes of Chicken (Gallus domesticus) Small Intestine Naturally Infected by Ascaridia galli - Ummu Balqis; Muhammad Hambal; Cut Syeila Utami (Jurnal Medika Veterinaria, 2014)
This study was aimed at finding out the histopathological changes of chicken small intestines that were naturally infected by Ascaridia galli. Ten intestines were obtained from wet market in Banda Aceh then measured in length and divided into three sections: duodenum, jejunum and ileum, of which histologic slides were made. The number of Ascaridia galli founded in the lumen and ingesta were counted. Parameter picture of histopathologycal changes were scored. Results were analyzed descriptively. Duodenum, jejunum and ileum infected by Ascaridia galli showed hyperemia, hemorrhage, desquamation, inflamatory cell infiltration, histopathological changes of villi represented by desquamation, hyperplasia and fusion. Damage level of the small intestine chicken was largely determined by the number of infecting Ascaridia galli. It was concluded that the more number of Ascaridia galli that infect chickens, the more damage occurred in the small intestine of chicken.Key words: intestine, chicken, Ascaridia galli